1989
DOI: 10.1099/00221287-135-3-583
|View full text |Cite
|
Sign up to set email alerts
|

Arsenical Resistance of Growth and Phosphate Control of Antibiotic Biosynthesis in Streptomyces

Abstract: Twenty-six wild-type Streptomyces strains tested for resistance to arsenate, arsenite and antimony(III) could be divided into four groups: those resistant only to arsenite (3) or to arsenate (2) and those resistant (8) or sensitive (13) to both heavy metals. All strains were sensitive to antimony. The structural genes for the ars operon of Escherichia coli were subcloned into various Streptomyces plasmid vectors. The expression of the whole ars operon in streptomycetes may be strain-specific and occurred only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This suggests that S. lividans 66 originally inhabited a niche where metals played a role, and this may be related to loss of the entire locus in TK24. Indeed, previous reports (Hänel et al 1989; Ravel et al 1998), and our own data, demonstrate that TK24 is sensitive to metals, including zinc, arsenic, mercury, and copper. TK24 metal sensitivity contrasts with the high metal tolerance exhibited by 66 for all four metals tested, and by M145 for zinc and arsenic (table 1 and supplementary fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…This suggests that S. lividans 66 originally inhabited a niche where metals played a role, and this may be related to loss of the entire locus in TK24. Indeed, previous reports (Hänel et al 1989; Ravel et al 1998), and our own data, demonstrate that TK24 is sensitive to metals, including zinc, arsenic, mercury, and copper. TK24 metal sensitivity contrasts with the high metal tolerance exhibited by 66 for all four metals tested, and by M145 for zinc and arsenic (table 1 and supplementary fig.…”
Section: Resultssupporting
confidence: 63%
“…Other sliGI-1 metal-related genes include the previously reported Streptomyces arsenic resistance ars operon (SLI1077–SLI1080; Wang et al 2006). The sliGI-1 ars operon is actually paralogous to a functional system conserved in the core region of the chromosome of many streptomycetes, including S. lividans and S. coelicolor (Hänel et al 1989). Interestingly, the duplicate ars operon is physically linked to a polyketide biosynthetic gene cluster (SLI1088–SLI1103) that is conserved in M145 and in S. coelicoflavus .…”
Section: Resultsmentioning
confidence: 99%
“…Ha «nel et al [7], reported that they could be sub-grouped according to their resistance to antimony, arsenate and arsenite, and the relative e¡ects of di¡erent heavy metals on growth and antibiotics production have been reported [8]. Following the detection of mercuric reductase in some streptomycetes [9], the structure of mercury resistance genes and their regulation have been studied in Streptomyces lividans [10].…”
Section: Introductionmentioning
confidence: 99%
“…Streptomycetes are Gram‐positive soil bacteria which can exhibit tolerance to metals and metaloids [6]. Hänel et al [7], reported that they could be sub‐grouped according to their resistance to antimony, arsenate and arsenite, and the relative effects of different heavy metals on growth and antibiotics production have been reported [8]. Following the detection of mercuric reductase in some streptomycetes [9], the structure of mercury resistance genes and their regulation have been studied in Streptomyces lividans [10].…”
Section: Introductionmentioning
confidence: 99%